Ultrafast Förster resonance energy transfer from tyrosine to tryptophan in monellin: potential intrinsic spectroscopic ruler. Issue 10 (28th February 2023) - Li, Haoyang; Cao, Simin; Zhang, Sanjun; Chen, Jinquan; Xu, Jianhua; Knutson, Jay R.
Abstract : Schematic diagram of ultrafast energy transfer from tyrosine to tryptophan in monellin. The three tyrosines close to tryptophan transfer energy to it by FRET. The energy transfer lifetime is ∼200 ps. Abstract : Ultrafast Förster Resonance Energy Transfer (FRET) between tyrosine (Tyr) and tryptophan (Trp) residues in the protein monellin has been investigated using picosecond and femtosecond time-resolved fluorescence spectroscopy. Decay associated spectra (DAS) and time-resolved emission spectra (TRES) taken with the different excitation wavelengths of 275, 290 and 295 nm were constructed via global analysis. At two of those three excitation loci (275 and 290 nm), earmarks of energy transfer from Tyr to Trp in monellin are seen, and particularly when the excitation is 275 nm, the energy transfer between Tyr and Trp clearly changes the signature emission DAS shape to that indicating excited state reaction (especially on the red side of fluorescence emission, near 380 nm). Those FRET signatures may overlap with the conventional signatory DAS in heterogeneous systems. When overlap and addition occur between FRET type DAS and "full positive" QSSQ (quasi-static self-quenching), mixed DAS shapes will emerge that still show "positive blue side and negative red sides", just with zero crossing shifted. In addition, excitation decay associated spectra (EDAS) taken with the different emission wavelengths of 330, 350 and 370 nm were constructed. In the study of protein dynamics, ultrafast FRET between Tyr and Trp could provide a basis for an intrinsic (non-perturbing) "spectroscopic ruler", potentially a powerful tool to detect even slight changes in protein structures.